2003
DOI: 10.4067/s0717-77122003000300003
|View full text |Cite
|
Sign up to set email alerts
|

Aislamiento de amebas de vida libre en piscinas públicas de Santiago de Chile

Abstract: The presence of free living Amoebae (FLA) was studied in samples of water obtained from 8 public swimming pool, collected from surface, bottom, channels, and filter. 8 samples for swimming pool, 64 samples in total. Amoebae were found in 5 swimming pool (62%). In 22 of the samples the Amoebae genus were identified (34.5%). These were Hartmanella vermiformes (12.5%); Vanella sp. (9.4%); Naegleria (7.8) and Acanthamoeba (4.7%).Considering the pathogenic capacity to man, the 36.4% of the isolated strains belonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
(1 reference statement)
0
9
0
1
Order By: Relevance
“…For instance, two Venezuelan [52] and five Brazilian [29] PAM cases have been registered. Regarding environmental isolations in this area, it has been conducted generally at genus level without assessing the diversity at the species level, as reports of Naegleria presence in public swimming pools of Santiago, Chile [53]. Thus, our molecular findings compose a large advance to broaden the knowledge on Naegleria diversity at environmental samples, mainly in the Brazilian scenario due its lack of FLA information.…”
Section: Naegleria Spp Diversity In Brazilmentioning
confidence: 99%
“…For instance, two Venezuelan [52] and five Brazilian [29] PAM cases have been registered. Regarding environmental isolations in this area, it has been conducted generally at genus level without assessing the diversity at the species level, as reports of Naegleria presence in public swimming pools of Santiago, Chile [53]. Thus, our molecular findings compose a large advance to broaden the knowledge on Naegleria diversity at environmental samples, mainly in the Brazilian scenario due its lack of FLA information.…”
Section: Naegleria Spp Diversity In Brazilmentioning
confidence: 99%
“…For instance, two Venezuelan [55] and five Brazilian [30] PAM cases have been registered. One additional Naegleria species has been identified in the public swimming pools of Santiago, Chile [56].…”
Section: Naegleria Spp Diversity In Brazilmentioning
confidence: 99%
“…The presence of Acanthamoeba strains in swimming pools has been documented in several studies (Rivera et al 1993, Tsvetkova et al 2004, Gianinazzi et al 2009). In Poland (Górnik and Kuzna-Grygiel 2004) and Finland (Vesaluoma et al 1995), acanthamoebae were detected in swimming pool water, and in Chile, several genera of amoebae were detected, including Acanthamoeba (Muñoz et al 2003). In Brazil, Chaves et al (1985) found acanthamoebae in swimming pools located in the city of Campo Grande, state of Mato Grosso do Sul, CentralWestern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In the Lagoa dos Patos estuary, Southern Brazil, Sassi et al (2010) detected the presence of Acanthamoeba in 91.7% (11/12) of the isolates obtained. Some authors report that these amoebae reach the pools through the water supply, by air or even by swimmers themselves (Muñoz et al 2003). In the state of Paraná, Southern Brazil, Ruthes et al (2004) diagnosed conjunctivitis caused by Acanthamoeba in four patients; one of them did not wear contact lenses but used to swim at the club weekly, which the authors suggested might have led to ocular infection with Acanthamoeba.…”
Section: Introductionmentioning
confidence: 99%